CATCHING A BUTTERFLY? Mapping eWork in Europe and Australia. (1st July 2007) - Peter Standen
Abstract : Drawing on the results of surveys carried out by the EMERGENCE project in 18 European countries in 2000 and Australia in 2002, this paper gives an overview of the relocation of telemediated work in Europe and Australia, highlighting the persistence of traditional regional and national locational patterns. It concludes by reflecting on some of the implications of the new possibilities for the relocation of telemediated work for regional policy.